Pseudo-patriotic undertone of unity discourse in Nigeria’s print media - Jibril, Ahmed Tanimu; Afida Mohamad Ali,; Zalina Mohamad Kasim,; Chan, Mei Yuit (Penerbit Universiti Kebangsaan Malaysia, 2021)
The realisation of genuine national unity within its ethnically diverse society has always been the primary challenge facing Nigeria since its Independence in 1960. This study investigated the discursive recontextualisation of national unity through newspaper congratulatory announcements (NCAs) within Nigeria’s ethnically diverse society, focusing on the pseudopatriotic undertones of the privately sponsored NCAs. Critical discourse analysis (CDA) and the agenda-setting theory informed the theoretical underpinning of the study. The data is drawn from four major dailies, covering the period between 2011 and 2016. Multimodal critical discourse analysis (MCDA) and the visual grammar (VG) are used as analytical methods to examine 97 privately sponsored NCAs. Dominant themes in the NCAs are highlighted along with the type of national unity projected in the NCAs. The analysis revealed that, in the name of promoting unity, private individuals and global conglomerates utilize pseudo acts to boost profits, enhance customer index, and construct their corporate image in the eyes of the ruling regimes and the general public in their host communities. It was also found that the envisioned future of the country as a united reality appears to contradict the common perception and lived experiences of the people. This study is meant to highlight the way certain ideologies are promoted and further interests are realised through the print media in the name of pseudo-patriotism. Further research may investigate comparable representations likely found in other newspaper genres as well as additional semiotic resources such as Nigeria’s Civil War artefacts and monuments, statues, and other national symbols.